Environmental risk factors of leishmaniasis in Bahia State, Brazil using NASA Earth observation satellites - de Santana Martins Rodgers, Moara; Emilia Bavia, Maria; Eichold II, Bernard; Shipman, Claire; Owen, Nathan; Winstanley, Hunter; Gordon, Margaret; Karapetyan, Marine; Mariana Nascimento Silva, Marta; Daniela Madureira Trabuco Carneiro, Deborah; et al. (Revista do Instituto Adolfo Lutz, 2019)
NASA’s Earth Observing Satellites (EOS) were used to calculate three vegetation indices, extract precipitation and elevation data, and then evaluate their applicability for assessing risk of visceral leishmaniasis (VL) and cutaneous leishmaniasis (CL) in Bahia State, Brazil. Regression models showed that either form of leishmaniasis can be predicted by NDVI, NDMI, NDWI data products and TRMM) precipitation data (R2= 0.370; p<0.001). Elevation was not significantly associated with the distribution of either VL or CL. In areas of high annual precipitation, CL was 3.6 times more likely to occur than VL. For vegetative moisture (NDMI), CL was 2.11 times more likely to occur than VL. Odds of CL occurrence increased to 5.5 times when vegetation (NDVI) and 13.5 times when liquid water content of vegetation canopies (NDWI) was considered. Areas at risk of CL and VL were mapped based on the selected explanatory variables. Accuracy of models were assessed using area under the receiver operating characteristic curve (AUC=0.72). We propose that statewide scale risk models based on use of EOS products will be a useful tool at 1 km2 spatial resolution to enable health workers to identify and target high risk areas to prevent transmission of leishmaniasis